SMM behavior in distorted trigonal bipyramidal and tetrahedral cobalt(II) complexes based on tripodal tetradentate phenolic amines - Massoud, Salah; Mautner, Franz A.; Sakiyama, Hiroshi; Louka, Febee R.; Salem, Nahed H. M.; Fischer, Roland C.; Torvisco, Ana; Guizouarn, Thierry; Velmurugan, Gunasekaran; Comba, Peter; Pointillart, Fabrice (European journal of inorganic chemistry, 2025)
Four CoII complexes [Co(L1)(MeOH)] ⋅ MeOH (1 ⋅ MeOH), [Co(L2)(MeOH)] ⋅ MeOH (2 ⋅ MeOH), [Co(L3)(H2O)] ⋅ MeOH (3 ⋅ MeOH) and [Co(L4)] (4), derived from tripodal tetradentate phenolic amine arms, H2L1-4 were synthesized and structurally characterized. The complexes 1 ⋅ MeOH, 2 ⋅ MeOH and 3 ⋅ MeOH displayed distorted trigonal bipyramidal geometry, whereas 4 exhibited distorted tetrahedral geometry, depending on the substituents at the phenolate rings and amine arm. The variation of the coordination geometries and interatomic parameters around the CoII center has an impact on the magnetic behavior of the compounds. The complexes show magnetic anisotropy (ZFS) of the MS= {± \ 1/2 and and {± \ 3/2 sub-levels, with D=29.1(2), 22.7(1), 28.8(2) and 30.9(5) cm−1 for 1 ⋅ MeOH, 2 ⋅ MeOH, 3 ⋅ MeOH and 4, respectively. The results obtained from ab initio CASSF calculations match well with the experimental data, revealing the origin of magnetic anisotropy. The dynamic ac magnetic investigation of the magnetic susceptibility revealed a slow magnetic relaxation behavior for 2 ⋅ MeOH, 3 ⋅ MeOH and 4. The field-induced slow relaxation of the magnetization occurred through combination of Raman and Direct processes, depending on the variation in the coordination geometries imposed by the coordinated ligand and/or the interatomic parameters around the CoII center, which in turn have definite impact on the magnetic features of the compounds.
Online veröffentlicht: 19. März 2025
Gesehen am 31.07.2025